The effect of a youth mental health service model on access to secondary mental healthcare for young people aged 14-25 years - Maxwell, S; Ugochukwu, O; Clarke, T; Gee, B; Clarke, E; Westgate, H; Wilson, J; Lennox, B; Goodyer, I (Cambridge University Press, 2018)
Aims and method The Norfolk Youth Service was created in 2012 in response to calls to redesign mental health services to better meet the needs of young people. The new service model transcends traditional boundaries by creating a single, ‘youth friendly’ service for young people aged 14–25 years. The aim of this study was to investigate the effect of the transition to this new model on patterns of referral, acceptance and service use. We analysed routinely collected data on young people aged 14–25 years referred for secondary mental healthcare in Norfolk before and after implementation of the youth mental health service. The number of referrals, their age and gender, proportion of referrals accepted and average number of service contacts per referral by age pre- and post-implementation were compared. Results Referrals increased by 68% following implementation of the new service model, but the proportion of referrals accepted fell by 27 percentage points. Before implementation of the youth service, there was a clear discrepancy between the peak age of referral and the age of those seen by services. Following implementation, service contacts were more equitable across ages, with no marked discontinuity at age 18 years. Clinical implications Our findings suggest that the transformation of services may have succeeded in reducing the ‘cliff edge’ in access to mental health services at the transition to adulthood. However, the sharp rise in referrals and reduction in the proportion of referrals accepted highlights the importance of considering possible unintended consequences of new service models. Declaration of interests None.